Dermatophytosis in domestic cats (Felis catus) positive to retrovirus - Ruiz, Andrea (2019)
The aim of this study was to isolate dermatophyte fungi from dermal lesions present in domestic cats (Felis catus) positive to immunodeficiency virus (FIV) and feline leukemia virus (FelLeF) retrovirals. Thirty-five felines were studied: 9 positives to FIV, 24 to VLeF and 2 to both viruses, patients of the veterinary clinic of the Santo Tomás University of Santiago de Chile. Hair and skin scale samples were obtained from skin lesions suspected of dermatophytosis, which were analyzed by direct microscopic examination and culture to identify mycotic agents. Results showed that 68.6% of the cats were diagnosed with dermatophytosis, Microsporum canis being the main isolated agent. The results indicate a significant association between the presence of dermatophytosis and the immunological compromise of the patients.